2008
DOI: 10.1121/1.2953309
|View full text |Cite
|
Sign up to set email alerts
|

Interference between wave modes may contribute to the apparent negative dispersion observed in cancellous bone

Abstract: Previous work has shown that ultrasonic waves propagating through cancellous bone often exhibit a linear-with-frequency attenuation coefficient, but a decrease in phase velocity with frequency (negative dispersion) that is inconsistent with the causality-imposed Kramers–Kronig relations. In the current study, interfering wave modes similar to those observed in bone are shown to potentially contribute to the observed negative dispersion. Biot theory, the modified Biot–Attenborogh model, and experimental results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 38 publications
(53 reference statements)
1
49
0
Order By: Relevance
“…Conventional phase spectroscopy analysis performed on mixed mode signals as if only one wave were present can yield apparent negative dispersion. 14,15,17 Previous work has demonstrated, however, that when decomposed, the fast wave and slow wave each exhibit positive dispersion. 19,27 Negative dispersion has been measured not only in trabecular bone [29][30][31][32][33] and cortical bone 34 in vitro but also in trabecular bone-mimicking phantoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional phase spectroscopy analysis performed on mixed mode signals as if only one wave were present can yield apparent negative dispersion. 14,15,17 Previous work has demonstrated, however, that when decomposed, the fast wave and slow wave each exhibit positive dispersion. 19,27 Negative dispersion has been measured not only in trabecular bone [29][30][31][32][33] and cortical bone 34 in vitro but also in trabecular bone-mimicking phantoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that interfering fast wave and slow wave modes can account for the apparent negative dispersion sometimes observed in measurements of cancellous bone. [13][14][15][16][17] This apparent negative dispersion arises when conventional phase spectroscopy analysis of two overlapping waves is performed as if only one wave were present. Sometimes the presence of an additional wave is not apparent in the RF signal.…”
Section: Introductionmentioning
confidence: 99%
“…22,[25][26][27][28][29][30][31][32] However, many laboratories report phase velocity measurements that decrease with frequency, a phenomenon known as anomalous negative dispersion. 2,6,8,[20][21][22][33][34][35][36][37] In an effort to explain the observed phase velocity dispersion, our Laboratory proposed that conventional phase spectroscopy analysis of acquired radiofrequency data might be influenced by the presence of multiple interfering compressional wave modes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some circumstances, the two waves can strongly overlap during the time period over which the rf data are acquired, resulting in interference and difficulties in distinguishing between the two waves. 5,15,17,18,20,21 Ultrasonic measurements from many laboratories have revealed that cancellous bone exhibits a linear or nearlylinear increase in attenuation coefficient with frequency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the existence of a second wave in cancellous bone has been reported in vitro Otani, 1997, 1998;Cardoso et al, 2001Cardoso et al, , 2003Mizuno et al, 2009). These two waves propagate with different velocities (Wear et al, 2005;Anderson et al, 2008Anderson et al, , 2009Wear, 2009;Nguyen et al, 2010;Wear, 2010) and have been shown to correspond to the fast and slow waves predicted by Biot's (Biot, 1941, 1955, 1956a,b, 1962a poroelastic wave propagation theory. Therefore, a poroelastic wave propagation theory is conceptually more appropriate than an equivalent media approach to characterize the properties of the porous medium.…”
Section: Introductionmentioning
confidence: 99%